2006
DOI: 10.1111/j.1464-410x.2006.06001.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘learning curve’ in hypospadias surgery

Abstract: OBJECTIVETo provide an insight into the 'learning curve' of fellowship-trained paediatric urologists associated with hypospadias repair, as hypospadias surgery is one of the most common yet difficult procedures used by the paediatric urologist. PATIENTS AND METHODSProspective data were collected on 231 consecutive hypospadias operations performed by one paediatric urologist (M.H.) over a 5-year period, beginning with his first year after completing his fellowship. All patients were having their first surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 24 publications
(21 reference statements)
3
22
0
2
Order By: Relevance
“…10,15 Our study supports this statement, as we demonstrated a decreasing complication rate as the surgeon's experience increased. In addition, the only other factor influencing TIPU outcomes was the initial meatal position.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…10,15 Our study supports this statement, as we demonstrated a decreasing complication rate as the surgeon's experience increased. In addition, the only other factor influencing TIPU outcomes was the initial meatal position.…”
Section: Discussionsupporting
confidence: 79%
“…8,15 One of the strengths of our study is that we can assume that all major complications were recorded in our charts due to the unavailability of another pediatric urologist within a reasonable distance. The complication rates observed in our study are similar to other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypospadias are arguably better off in experienced hands in terms of short-term complications [36,37]. Whether this is also true for long-term results is uncertain, but more experienced centers do contain higher volumes of patients eligible for follow up.…”
Section: Futurementioning
confidence: 93%
“…Our data suggest that the learning curve and the personal experience of the surgeon could be important in achieving satisfactory results [15,16]. Therefore, the quality of the surgeon or the quality of the procedure is considered the most relevant factor to explain the difference.…”
Section: Discussionmentioning
confidence: 87%